The significance of transformational leadership in pursuing gender parity in the Department of Social Development, Sekhukhune District in Limpopo Province - Mokomane, Kgonthe Melisa (My University, 2017)
This study drew attention to the influential role the transformational leadership constructs can play in increasing women representation in decision making structures of the Department of Social Development (DSD). The DSD’s Sekhukhune District in Limpopo Province was used as an area of study. The aim of the study was to investigate the significance of transformational leadership in pursuing gender parity in the DSD’s Sekhukhune District. The study followed an exploratory research design and implemented a qualitative methodology. A total of 10 DSD managers were targeted. Furthermore, a purposive sampling was used and interviews were conducted as the method of data collection. The data collected had been analysed thematically. The results revealed that although there have been improvements of more appointed women managers within the organisation. There were still more women managers than men managers within the organisation. However, most men occupy senior management positions while most women occupy the lower managerial positions. Most managers were not inspired to perform more than they were expected giving the reason that, they lack resources and their efforts often go unrecognised. Most managers found political appointment discouraging towards fair promotions. Nevertheless, there were enough women who possess required leadership skills. Conversely, there were no programmes that support women participation and empowerment in issues relating to gender parity. Leadership training, transformational leadership, provision of resources and salary acceleration were common suggestions to pursue gender parity. The study recommends that the DSD Sekhukhune District leadership should adopt and implement transformational leadership, change political appointment, appoint leaders with relevant qualifications, establishing a functional gender mainstreaming office within the DSD Sekhukhune District, adequate budgetary support and specialised training of staff shall assist in closing the gender parity gap.
Thesis (MBA.) --University of Limpopo, 2017
Keywords: Transformational leadership; Women representation; Gender parity; Leadership in minority women; Transformational leadership; Women in development -- South Africa